Internal migrant trajectories within The Netherlands, 1850–1972: Applying cluster analysis and dissimilarity tree methods. Issue 3 (3rd July 2022) - Sesma Carlos, Dolores; Kok, Jan; Oris, Michel
Abstract: Based on the life course perspective, this work adopts a sequence analysis approach to examine internal migrant trajectories and their interdependencies with life course factors. The analyses are based on longitudinal data from the Historical Sample of the Netherlands. The internal migrant trajectories of Dutch cohorts born between 1850 and 1922 are followed from birth until age fifty. Two sequence analysis methods are applied: (1) main migration patterns are described using cluster analysis, and explained by their associations with socio-demographic covariates using logit models; (2) migrant trajectory variations are investigated using a dissimilarity tree method with a discrepancy analysis. Seven distinct migrant trajectory patterns are derived from the cluster analysis. Early-life social status, place and region of origin are differently associated to these typologies, and an increased stability of specific trajectories over time is suggested. Fifteen homogeneous migrant trajectories are identified in the dissimilarity tree. The discrepancy between groups is explained by intricate interactions between birth cohort, social and place origin, as well as family formation. The cluster analysis suggests a stable regime of internal migration patterns over time. The dissimilarity tree method contributes to detect interdependencies of migrant trajectories, highlighting socio-economic, local and regional differences at birth.